Information Disseminated by Spore 3 - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
RITA (Reseau d'lnformation des Terres Arides) Dakar, Senegal: ' In a recent edition of SPORE there was a short and very concise article about RITA. I would like to inform you that we have received 35 enquiries to date /20.5.96) as a result of the...